Association between pain, central sensitization and anxiety in postherpetic neuralgia. (28th July 2014) - Schlereth, T.; Heiland, A.; Breimhorst, M.; Féchir, M.; Kern, U.; Magerl, W.; Birklein, F.
Abstract Background In postherpetic neuralgia (PHN), dorsal root ganglia neurons are damaged. According to the proposed models, PHN pain might be associated with nociceptive deafferentation, and peripheral (heat hyperalgesia) or central sensitization (allodynia). Methods In 36 PHN patients, afferent nerve fibre function was characterized using quantitative sensory testing and histamine‐induced flare analysis. Psychological factors were evaluated with the Hospital Anxiety and Depression Scale (HADS), disease‐related quality of life (QoL) with SF‐36 and pain with the McGill questionnaire [pain rating index (PRI)]. The patients were also divided into subgroups according to the presence or absence of brush‐evoked allodynia as a sign of central sensitization. Results For all patients, warm, cold and mechanical detection was impaired (p < 0.001 each) and the size of the histamine flare was diminished on the affected side (p < 0.05); pain thresholds with the exception of brush‐evoked allodynia (p < 0.05) were unaltered. Correlation analysis revealed allodynia, anxiety, depression, QoL and age as relevant factors associated with pain severity (PRI). Allodynia was present in 23 patients (64%). In these patients, heat pain perception was preserved; the histamine flare was larger; the pinprick pain was increased as were McGill PRI sensory subscore, actual pain rating and almost significantly pain (McGill PRI) over the last 4 weeks. Conclusions PHN is associated with damage of afferent fibres. Central sensitization (i.e., allodynia) might contribute to PHN pain. There was a striking association between anxiety, depression and age, and the magnitude of PHN pain.